TAHAPAN STRATEGI DAN TAKTIK MEDIA SOSIAL INSTAGRAM HEAL YOURSELF - Febrianti, Tantri; Hafiar, Hanny; Perbawasari, Susie (JURNAL SIGNAL, 2023)
Instagram is a social media platform that is currently loved by the public. The large number of active users on Instagram has led to companies, communities, or agencies starting to use Instagram to inform or promote products and even activities carried out by companies via Instagram social media. This research aims to determine the situation, goal setting, target audience, strategy, tactics, timeline, and budget on Heal Yourself Instagram social media. The method used in this research is a descriptive research method with a qualitative approach. The data collection techniques used were observation, interviews, and literature study. The results of this research show that the current situation is that various fields are moving towards digital, including in conveying messages, as well as the increasing prevalence of radical social media accounts, in setting the goal to campaign for mental health and Islamic self-help. The target audience set is young adults aged 20-30 years in the cities of West Java. The strategies implemented are interactive classes, counselling services, special events, and social media activation. The tactics used start from identifying problems in the field, discussing with the Content Creator, designing, and uploading content. The language used on Instagram social media is non-formal language. Heal Yourself has not set a specific timeline for managing their Instagram social media. Heal Yourself still needs to set a specific budget for its social media. Apart from that, we have yet to use influencers or buzzers on Heal Yourself's Instagram social media. Keywords: social media, social media strategy, social media planning